Olhar a pobreza em Angola: causas, consequências e estratégias para a sua erradicação - Sílvia de Oliveira (Ciências Sociais Unisinos)
The phenomenon of poverty has been widely debated in these last years. Yet, its eradication is still far away from being materialized. The lack of access to the satisfaction of basic needs such as food, education, employment, drinking water, sanitation, among others, forces the large majority of the African people in general and the Angolans in particular to live in extreme inhuman conditions. In Angola, in spite of the fact that the armed conflict finished more than ten years ago, the living conditions of the Angolan people are still precarious.